(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study involves an empirical analysis of factors influencing cash holding by MSME’s manufacturing substitutes for defence aviation sub-assemblies in India. Quantitative research methodology with correlation design establishes the relation between cash holding and the components of working capital. The univariate data analysis indicates that cash and cash equivalents constitute 14.14%, inventory 24% and trade receivables 42 % of the current assets. The panel data regression analysis with trade receivables as the independent variable explains 50 % of the variability of cash holding and has significant impact on cash holding. The research is unique as it focuses on the relationship of cash holding with the working capital components for low volume labour intensive project nature of manufacturing by the MSMEs.